Powder Metallurgical Processing of Al–5 Wt% Cu Matrix Composites Reinforced With Mosi2 and Wsi2 Particulates - Mertdinç-Ülküseven, S.; Ovalı-Döndaş, D.; Süzer, İ.; Altıntaş, M.; Can Karaca, M.; Özal, B.; Öveçoğlu, Mustafa Lütfi; Karaca, Murat Can (John Wiley and Sons Inc, 2024)
Herein, investigations on the microstructural, physical, and mechanical properties of molybdenum disilicide (MoSi2)- and tungsten disilicide (WSi2)-reinforced aluminum (Al)–copper (Cu) matrix composites are reported. Powder metallurgy methods such as mechanochemical synthesis (MCS), mechanical alloying (MA), cold pressing, and pressureless sintering are combined to produce composites. First of all, MoSi2 and WSi2 nanoparticles are synthesized by MCS and selective acid leaching, yielding reinforcement materials for Al–Cu matrix. Powder blends consisting of 95 wt% Al and 5 wt% Cu are mixed with metal disilicides at different weight percentages (1, 2, and 5 wt%). MA for 4 h is conducted on these overall blends using a high-energy ball mill. Microstructural and thermal properties of the as-blended and mechanically alloyed powders are determined, and then they are compacted under 450 MPa and sintered at 550 °C for 2 h. Mechanical characterization of the composites reveals an increase in hardness and wear resistance with an increasing amount of reinforcement content. Among bulk samples, 5 wt% WSi2-reinforced composites have the highest microhardness (165 ± 15 HV) and lowest wear rate (1.69 × 106 μm3 Nm−1) values. However, under the compression forces, the highest toughness and strength are obtained from 2 wt%-reinforced composites. © 2024 Wiley-VCH GmbH.
Keywords: Al–Cu Metal Matrix Composites; Mechanical Alloying; Molybdenum Disilicides; Pressureless Sintering; Tungsten Disilicides; Al-Cu Metal Matrix Composites